The Influence of Beauty Influencers, Product Quality, and Brand Image on Green Skincare Purchasing Decisions of Avoskin Consumers in Bandar Lampung - Sahprada, Nabila Trias; Arif Sugiono; Winda Septiani (International Journal of Economics, Business and Innovation Research, 2025)
Avoskin customers in Bandar Lampung are the focus of this study, which seeks to understand how beauty influencers, product quality, and brand image impact green skincare purchase decisions. Data for this study came from a questionnaire that was randomly selected using an incidental sampling methodology; the research method used was quantitative and explanatory. Using test methodologies such as outer model testing, inner model testing, and hypothesis testing, data analysis was conducted using MS Excel and SmartPLS 4.0 software. The study found that Avoskin customers' purchase decisions of green skincare are influenced to some extent by beauty influencers, product quality, and brand image. Furthermore, these three factors impact consumers' choices to buy at the same time.